PENGARUH SANITASI LINGKUNGAN SPAL (SALURAN PEMBUANGAN AIR LIMBAH) TERHADAP KEJADIAN PENYAKIT DBD (DEMAM BERDARAH DENGUE) - Susilawati Susilawati; Siti Nurzannah (CV. ADIBA AISHA AMIRA, 2023)
Introduction: Sanitation is an important factor in public health. One of the areas that has a fairly high level of difficulty in managing sanitation is the coastal area where the main problem lies in the disposal of household waste and garbage as an environmental sanitation problem. Healthy housing is a gathering place for all family members and spends most of their time. so that the health conditions of housing can act as a medium for disease transmission among family members or neighbors, especially the people in coastal areas whose household wastewater channels are considered for healthy housing. Methods: To obtain data on research methods using a comprehensive search-based Systematic Review based on 3 open science framework OSF indexed journals, Medline Pubmed, and Google Scholar. The research sample uses 12 journal references. Result: Community knowledge regarding household wastewater disposal is still minimal because the community has never received health education or information regarding household wastewater disposal. Facilities for disposing of liquid waste in households include disposal of water used for kitchen, bathroom and hand washing facilities. So that a waste water disposal channel (SPAL) is needed in the form of a pipe or other in order to become a place for disposal of waste water from the source to the place of management. Conclusion: There is a significant influence of sewage drainage on the incidence of Dengue Hemorrhagic Fever (DHF).